Dalihan Na Tolu (DNT) Sebagai Rekonsiliasi Konflik Agama Islam-Kristen Dalam Masyarakat Batak - Zulkarnain Siagian; Ewen Josua Silitonga (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2023)
Batak society is heterogeneous in embracing religion, in particular, most Batak people embrace Islam and Christianity, and in the historical context of Islam-Christian relations and interactions experience conflict. The study is conducted with a culture-based conflict reconciliation methodology with a library research method, looking for documents, books or literature related to the topic. Dalihan Na Tolu (DNT) as the pulse of Batak custom is able to unite religious differences in the Batak tribe in the public sphere, so DNT needs to be developed as conflict reconciliation due to religious differences in Batak society, especially Islam-Christianity.